Evaluation of green roof system for green building projects in Malaysia - Fauzi, Muhammad Ashraf; Abdul Malek, Nurhayati; Othman, Jamilah (World Academy of Science, Engineering and Technology (W A S E T), 2013)
The implementations of green roof have been widely used in the developed countries such as Germany, United Kingdom, United States and Canada. Green roof have many benefits such as aesthetic and economic value, ecological gain which are optimization of storm water management, urban heat island mitigation and energy conservation. In term of pollution, green roof can control the air and noise pollution in urban cities. The application of green roof in Malaysian building has been studied with the previous work on green roof either in Malaysia or other Asian region as like Indonesia, Singapore, Thailand, Taiwan and several other countries that have similar climate and environment as in Malaysia. These technologies of adapting green roof have been compared to the Green Building Index (GBI) of Malaysian buildings. The study has concentrated on the technical aspect of green roof system having focused on i) waste & recyclable materials ii) types of plants and method of planting and iii) green roof as tool to reduce storm water runoff. The finding of these areas will be compared to the suitability in achieving good practice of the GBI in Malaysia. Results show that most of the method are based on the countries own climate and environment. This suggests that the method of using green roof must adhere to the tropical climate of Malaysia. Suggestion of this research will be viewed in term of the sustainability of the green roof. Further research can be developed to implement the best method and application in Malaysian climate especially in urban cities and township.